Receptor of advanced glycation end product (RAGE) polymorphism and oxidative status in Hashimoto’s thyroiditis in Egyptian female patients: case control study - Noura Mostafa Mohamed; Azza H. Abd elfatah (Egyptian Journal of Medical Human Genetics, 2022)
Abstract Background Hashimoto's thyroiditis is the most widespread autoimmune illness targeting a specific organ. "Redox homeostasis" is achieved when the production of Reactive Oxygen Species and their elimination are in balance. Advanced glycation end products (AGEs) are formed when glucose and/or α-oxaloaldehydes react non-enzymatically with the amino groups of lipids, proteins, and DNA. Nowadays, many studies are concerned with AGEs, the polymorphisms of their receptors, and their association with increased risk of HT. However, few studies investigated the role of receptors of advanced glycation end product (RAGE) SNP in Egyptian females. Objective The goals of this investigation were to ascertain whether oxidative stress plasma malondialdehyde (MDA) and total antioxidant capacity (TAC) were associated with HT, in addition, to assess the association of RAGE polymorphisms (− 374 T > A and the − 429 T > C and Gly82Ser) with HT. Subject and methods. Our case–control study has 80 patients enrolled who have newly been diagnosed with HT and 80 age and sex-matched healthy female controls. Each participant underwent a thorough medical history, physical examination, and laboratory investigations, which included Genotyping of RAGE Gly82Ser, − 374 T > A and − 429 T > C using polymerase chain reaction-restriction fragment length polymorphisms (PCR–RFLP). Results Chi-square revealed a significant association regarding the distribution of RAGE (− 374 T < C) genotypes TT and CC between patients and control (P = 0.04). Non-significant associations regarding the distribution of Gly82Ser genotypes Gly/Gly, Gly/Ser, Ser/Ser were found between patients and control (P = 0.5), and non-significant associations related to − 429 T > C gene polymorphism were revealed. In addition, patients with HT had higher MDA and lower TCA compared with controls. Conclusion The elevated MDA and decreased TAC as an antioxidant may be one of several risk factors associated with the prevalence of HT in individuals with the − 429 T > C RAGE mutation polymorphism that is associated with an increased risk of HT in Egyptian females.